Metoprolol Induced Psoriasis: A Case Report - Inamdar, Syed Zia; Katragadda, Pradeepthi; Sasikumar, Ammu; Mohan, Akhila; Kulkarni, Raghavendra Vinayakarao (Indian Journal of Pharmacy Practice)
Metoprolol, an antihypertensive drug belonging to the class β 1 receptor blocker inhibits adrenergic receptors in heart muscle cells and decreases heart rate, contractility and cardiac output thereby decreases the blood pressure. Though, the drug have been approved for the treatment of blood pressure and arrhythmias, the safety profile of it is not yet established in a broader sense. A patient with known hypertensive diagnosis and presenting complaints of bilateral swelling over lower limbs since 15 days and skin lesions over the body since 5 days was admitted to the medicine ward of a tertiary care hospital. After careful evaluation of the patient, the skin lesion was found to be chronic plaque psoriasis of a drug induced nature, which was then treated symptomatically. The suspected drug metoprolol was discontinued. A Naranjo causality assessment of the observed reaction reveals a “probable” causal relationship and rated under “moderate” severe adverse reaction category as per Hartwig’s severity assessment.
Keywords: Adverse Drug Reaction; Skin Lesions; Metoprolol; Chronic Plaque Psoriasis.